Myoelectric Knee Angle Estimation Algorithms for Control of Active Transfemoral Leg Prostheses - Delis, Alberto L.; Carvalho, Joao L. A.; Rocha, Adson F. da; Nascimento, Francisco A. O.; Borges, Geovany A. (IntechOpen, 2011)
None